P111 Chest drain troubleshooting by trainee physicians: an easily deliverable multi-component training module. (12th November 2019) - Patel, T; Munro, A; Hettiarachchi, G; Sarkar, R
Abstract : Introduction: Intercostal chest drains (ICD) are a common medical intervention used in acute medical wards, respiratory wards and sometimes in surgical wards. Despite this, sound understanding of troubleshooting chest drain related issues could be lacking among junior medical staff. Objective: We aimed to develop a comprehensive educational module for ICD troubleshooting aimed at Foundation doctors. Methods: The training module, with a duration of 2 hours, was planned in 4 different components: 1. A Lecture including a video explaining steps looking after an ICD, detailed assessment of an ICD circuit and common problems. 2. A low fidelity simulation, aided by a working ICD model, explaining ICD troubleshooting, both for pneumothorax and pleural effusion. 3. High fidelity simulation, followed by debrief, based on a real life recent hospital scenario, where the trainees could practice the knowledge they have just gained, alongside utilising team based skills relevant for the scenario. 4. An end-of-session summary of the knowledge/skill gained, and a clinical scenario based quiz to guide the trainees to address their knowledge gaps they might still have. Pre and post-module Likert scale (scale of 1–10, 1=not confident at all, 10=fully confident) questionnaire were used to measure trainees' confidence and competence of ICD management. Results: Thirty-eight foundation doctors took part in the module. In answering how confident they felt in managing an acutely hypoxic patient with an ICD, the average pre-module score on Likert scale were 3/10 in both FY1 and FY2 groups, rising to 7/10 in each group in the post-module questionnaire. Answering how they felt in general troubleshooting on ICD, in pre-module questionnaire, 41% felt not-at-all competent, 41% wanted direct supervision and 17% felt they could manage under indirect supervision. Post-module, 30% felt independent, 57% could manage under indirect supervision and only 13% still felt that they needed direct supervision. They also felt significantly more confident in identifying the cause of deterioration in a patient with ICD, if the aetiology was related to ICD circuit. They felt the high fidelity simulation consolidated the learning. Conclusion: A short 2 hour multi-component training module, that includes traditional teaching methods, alongside low and high fidelity simulation, could be a useful method to build confidence around ICD management amongst trainee doctors.